Boron nitride-containing resin composition and application thereof
By modifying the combination of boron nitride and resin material, the problem of difficult to take into account the thermal conductivity and adhesion of copper clad plates is solved, and a metal-covered foil laminate with high thermal conductivity and high reliability is achieved.
Patent Information
- Application Number
- CN202411948084.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The existing copper clad plates are difficult to take into account both thermal conductivity and adhesion, resulting in insufficient thermal conductivity and reduced reliability.
Modified boron nitride is prepared by mixing boron nitride with a sintering aid for sintering and crushing, and combined with a resin material to form a boron nitride-containing resin composition to improve its fill rate and performance in the metal-covered foil laminate.
The excellent comprehensive effect of metal foil laminate in high thermal conductivity and high reliability is achieved, with high thermal conductivity, excellent bonding properties and high peel strength.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-clad laminates, and particularly relates to a boron nitride-containing resin composition and application thereof. Background Art
[0002] With the continuous development of electronic products, the power consumption of devices is getting bigger and bigger, and the heat per unit area during working time is getting more and more. In order to ensure the working stability of electronic components, the heat dissipation requirements of the board are getting higher and higher. Poor heat dissipation of the board will reduce the reliability of the whole machine, and even cause product failure and shorten the service life of the product.
[0003] In order to meet the heat dissipation requirements of the board, dielectric layers and copper-clad laminates with high thermal conductivity are the research and development focus in the industry. For example, CN101767481A discloses a method for preparing a high thermal conductivity copper-clad laminate, which includes the following steps: by mass content, 60-90% of multifunctional epoxy resin is mixed with 10-40% of polyurethane to prepare a resin glue solution with a solid content of 60-90%; dicyandiamide is used as a curing agent and 2-methylimidazole is used as an accelerator to prepare a glue solution with a gel time of 150-450s, and a mixture of 40-60% aluminum nitride and 40-60% aluminum oxide is used as a filler of the glue solution; the glue solution is used to impregnate glass cloth to form a bonding sheet, and then multiple bonding sheets are stacked and coated with copper foil, and hot pressed to form a high thermal conductivity copper-clad laminate. CN110370750A discloses a high thermal conductivity copper clad laminate, comprising a core thermal conductive adhesive sheet and a surface thermal conductive adhesive sheet, wherein the core thermal conductive composition for preparing the core thermal conductive adhesive sheet comprises the following raw materials: 10-35 parts of bisphenol A epoxy resin, 5-10 parts of curing agent, 50-80 parts of filler, and 10-30 flame retardant; the surface thermal conductive composition for preparing the surface thermal conductive adhesive sheet comprises the following raw materials: 10-35 parts of surface epoxy resin, 5-10 parts of curing agent, 30-50 parts of filler, and 10-30 parts of flame retardant; the filler in the core material and the surface is a mixture of aluminum oxide and boron oxide in a mass ratio of 1:1. CN115556439A discloses a low-dielectric and high-thermal-conductivity polytetrafluoroethylene high-frequency copper-clad laminate, which is prepared by laminating a dielectric layer and a copper foil and pressing them at high temperature. The dielectric layer includes 10-20% of a fluorine resin emulsion, 3-6% of a silane coupling agent, 2-7% of a fiber reinforcement material, and the rest is a thermally conductive filler, and the thermally conductive filler includes 10-30% of layered boron nitride, 20-35% of silicon powder, 10-15% of aluminum nitride and 10-35% of spherical aluminum oxide.
[0004] At present, the thermal conductive filling materials commonly used in copper clad laminates mainly include boron nitride, aluminum oxide, aluminum nitride, boron oxide, etc. Among them, boron nitride has excellent performance in thermal conductivity, but it has a lamellar structure and a large specific surface area, and cannot be filled in large quantities in the resin, which greatly weakens the ability of boron nitride to improve the thermal conductivity of composite materials. In addition, the increase in the amount of thermal conductive filling materials will also lead to the deterioration of the adhesion between the glue layer and the copper foil and the metal substrate, which will have a negative impact on a series of properties of the copper clad laminate such as heat resistance and voltage resistance, and the reliability will deteriorate.
[0005] Therefore, how to obtain a composite material with both high thermal conductivity and excellent adhesion is a problem to be solved urgently in this field. Summary of the invention
[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a boron nitride-containing resin composition and its application. By designing a modification method, the modified boron nitride has a high filling rate in the resin material. The boron nitride-containing resin composition containing the modified boron nitride has not only high thermal conductivity, but also excellent bonding performance and high peel strength, so that the metal foil-clad laminate achieves excellent comprehensive effects in terms of high thermal conductivity and high reliability.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a boron nitride-containing resin composition, wherein the boron nitride-containing resin composition comprises a combination of a resin material and modified boron nitride.
[0009] The modified boron nitride is prepared by the following method, which includes: mixing boron nitride and a sintering aid, sintering and crushing to obtain the modified boron nitride; wherein the sintering aid includes any one of calcium oxide, magnesium oxide, silicon oxide, yttrium oxide, niobium oxide, and potassium feldspar, or a combination of at least two thereof; based on the total mass of the boron nitride and the sintering aid being 100%, the mass of the sintering aid is 1-10%.
[0010] The present invention subjects boron nitride and a sintering aid to high-temperature sintering and crushing to obtain the modified boron nitride particles. Under the synergistic effect of the sintering aid and sintering, the filling ratio of the modified boron nitride particles in the resin material can be increased, so that the boron nitride-containing resin composition has high thermal conductivity, high peel strength, and excellent bonding performance, thereby significantly improving the comprehensive performance of the metal foil-clad laminate in terms of heat dissipation and reliability.
[0011] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0012] Preferably, the boron nitride includes any one of hexagonal boron nitride and cubic boron nitride or a combination of at least two of them, more preferably hexagonal boron nitride.
[0013] In the present invention, taking the total mass of the boron nitride and the sintering aid as 100%, the mass of the sintering aid is 1-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0014] The present invention mixes a specific type and amount of sintering aid with boron nitride, and then sintering and crushing to obtain a specific modified boron nitride, which overcomes the defect that lamellar boron nitride cannot be filled in large quantities, resulting in insufficient thermal conductivity of the material. The modified boron nitride has excellent thermal conductivity and a high filling rate in the resin material, so that the boron nitride-containing resin composition containing it has both high thermal conductivity and high peel strength. If the amount of the sintering aid is less than 1%, it is difficult to effectively modify the boron nitride and the filling ratio of boron nitride in the resin cannot be increased; if the amount of the sintering aid is greater than 10%, the thermal conductivity of the modified boron nitride and the boron nitride-containing resin composition containing it will be significantly reduced.
[0015] Preferably, the mixed raw materials further include other metal oxides.
[0016] In the present invention, the "other metal oxide" refers to a metal oxide other than the sintering aid.
[0017] Preferably, the other metal oxides include aluminum oxide and / or beryllium oxide.
[0018] Preferably, taking the total mass of the boron nitride, sintering aids and other metal oxides as 100%, the mass of the other metal oxides is 1-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8% or 9%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0019] Preferably, the mixing method comprises physical dry mixing.
[0020] Preferably, the mixing time is 0.1-3h, for example, it can be 0.2h, 0.4h, 0.5h, 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h or 2.8h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0021] Preferably, the sintering is performed in an inert atmosphere.
[0022] Preferably, the inert atmosphere includes a nitrogen atmosphere and / or an argon atmosphere.
[0023] Preferably, the sintering temperature is 700-2000°C, for example, it can be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C or 1900°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0024] Preferably, the sintering pressure is 1-10 GPa, for example, it can be 2 GPa, 3 GPa, 4 GPa, 5 GPa, 6 GPa, 7 GPa, 8 GPa or 9 GPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0025] Preferably, the sintering time is 2-8h, for example, it can be 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h or 7.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0026] As a preferred technical solution of the present invention, the sintering is carried out in an inert atmosphere. By controlling the sintering temperature to 700-2000°C, the pressure to 1-10GPa, and the time to 2-8h, the filling ratio of the modified boron nitride in the resin material can be further optimized.
[0027] Preferably, the crushing method includes ball milling, for example, wet ball milling.
[0028] Preferably, the rotation speed of the ball mill is 500-5000rpm, for example, it can be 1000rpm, 1500rpm, 2000rpm, 2500rpm, 3000rpm, 3500rpm, 4000rpm or 4500rpm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0029] Preferably, the ball milling time is 0.5-6h, for example, it can be 0.8h, 1h, 1.2h, 1.5h, 1.8h, 2h, 2.2h, 2.5h, 2.8h, 3h, 3.2h, 3.5h, 3.8h, 4h, 4.2h, 4.5h, 4.8h, 5h or 5.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0030] Preferably, the average particle size of the modified boron nitride is 0.1-30 μm, for example, it can be 0.2 μm, 0.5 μm, 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm or 28 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0031] In the present invention, the average particle size can be understood as D 50 Particle size, relevant data of particle size can be obtained by testing using MS3000 Malvern laser particle size analyzer.
[0032] In the present invention, the mass percentage of modified boron nitride in the boron nitride-containing resin composition can be adjusted according to the requirements of thermal conductivity, processability of the board, peel strength, reliability and other properties, and can be 20-92%.
[0033] Preferably, the mass percentage of modified boron nitride in the boron nitride-containing resin composition is 30-92%, for example, it can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 50-90% is further preferred.
[0034] As a preferred technical solution of the present invention, the mass percentage of modified boron nitride in the boron nitride-containing resin composition is 30-92%, and more preferably 50-90%, thereby making the boron nitride-containing resin composition and the metal foil-clad laminate prepared therefrom have high thermal conductivity, high bonding performance and excellent reliability. If the content of modified boron nitride is too low, the thermal conductivity will be reduced; if the content of modified boron nitride is too high, the processability of the resin composition will be deteriorated, and it will be difficult to obtain a qualified plate.
[0035] Preferably, the resin material includes any one of epoxy resin, cyanate resin, polyphenylene ether resin, polybutadiene resin, butadiene-styrene resin, bismaleimide-triazine resin, bismaleimide resin, polytetrafluoroethylene resin, polyimide resin, phenolic resin, phenoxy resin, acrylic resin, liquid crystal resin, benzoxazine resin, and nitrile rubber, or a combination of at least two of them.
[0036] Preferably, the nitrile rubber includes any one of unmodified nitrile rubber, carboxyl-terminated nitrile rubber, and hydroxyl-terminated nitrile rubber, or a combination of at least two thereof.
[0037] Further preferably, the resin material includes any one of epoxy resin, polyphenylene ether resin, polybutadiene resin, styrene-butadiene resin, bismaleimide resin, phenolic resin, and phenoxy resin, or a combination of at least two thereof.
[0038] Preferably, the epoxy resin includes any one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, novolac epoxy resin, biphenyl epoxy resin, phenol novolac epoxy resin, bisphenol A novolac epoxy resin, silicone-modified epoxy resin, phosphorus-containing epoxy resin, brominated epoxy resin, aliphatic epoxy resin, alicyclic epoxy resin, o-cresol epoxy resin, and dicyclopentadiene (DCPD) epoxy resin, or a combination of at least any two thereof.
[0039] Preferably, the polyphenylene ether resin is a polyphenylene ether having a terminal group containing a C=C unsaturated bond, and more preferably a polyphenylene ether having a terminal group containing any one or at least two of vinylbenzyl, vinylphenyl, acrylate, and methacrylate groups.
[0040] Preferably, the polybutadiene resin and the styrene-butadiene resin both contain cross-linkable active groups C=C, such as 1,2-vinyl based on butadiene monomers.
[0041] Preferably, the mass percentage of the resin material in the boron nitride-containing resin composition is 8-80%, for example, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 75%, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 9-50% is further preferred.
[0042] In a preferred technical solution, the boron nitride-containing resin composition comprises the following components in terms of mass percentage: 4-50% epoxy resin (e.g., 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%, etc.), 0-10% phenoloxy resin (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 4%, 5%, 6% or 8%, etc.), and 40-92% modified boron nitride (e.g., 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.).
[0043] In another preferred technical solution, the boron nitride-containing resin composition comprises the following components by mass percentage: 4-50% hydrocarbon resin (e.g., 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%, etc.), 0-10% polyphenylene ether resin (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 4%, 5%, 6% or 8%, etc.), and 40-92% modified boron nitride (e.g., 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc.).
[0044] In another preferred technical solution, the boron nitride-containing resin composition comprises the following components in mass percentage: 4-50% (e.g., 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%) of polyphenylene ether resin, 0-10% (e.g., 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 4%, 5%, 6% or 8%) of hydrocarbon resin, and 40-92% (e.g., 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%) of modified boron nitride.
[0045] Wherein, the hydrocarbon resin includes polybutadiene resin and / or styrene-butadiene resin, preferably polybutadiene resin.
[0046] Preferably, the boron nitride-containing resin composition further comprises any one of an accelerator, an initiator, a cross-linking agent, a filler, a flame retardant, and a curing agent, or a combination of at least two thereof.
[0047] Preferably, the accelerator includes any one of imidazole compounds, organic complexes, tertiary amines, tertiary phosphines, and quaternary ammonium salts, or a combination of at least two thereof, and imidazole compounds are further preferred.
[0048] Preferably, the imidazole compound includes any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 2-isopropylimidazole, 2-phenyl-4-methylimidazole, 2-dodecylimidazole, and 1-cyanoethyl-2-methylimidazole, or a combination of at least two thereof.
[0049] Preferably, the mass percentage of the accelerator in the boron nitride-containing resin composition is ≤8%, for example, it can be 0, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0050] Preferably, the initiator includes any one of an organic peroxide, an azo initiator, and a carbon-based initiator, or a combination of at least two of them.
[0051] Preferably, the organic peroxide includes any one of α,α'-di(tert-butylperoxy-m-isopropylbenzene)benzene, diisopropylbenzene peroxide, tert-butylperoxy-isopropylbenzene, bis(tert-butylperoxy-isopropyl)benzene, 1,1-bis(tert-hexylperoxide)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, tert-butyl peroxyoctanoate, and tert-butyl peroxybenzoate, or a combination of at least two thereof.
[0052] Preferably, the initiator further comprises any one of triethylamine, triethylamine salt compounds, quaternary amine salt compounds, 2,4,6-tris(dimethylaminomethylamine)phenol, benzyldimethylamine, imidazoles, tripentylphenol amine, monophenol compounds, polyphenol compounds, boron trifluoride, boron trifluoride organic complexes, triphenyl phosphate, and triphenyl phosphite, or a combination of at least two thereof.
[0053] Preferably, the mass percentage of the initiator in the boron nitride-containing resin composition is ≤8%, for example, it can be 0, 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7% or 7.5%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0054] Preferably, the crosslinking agent includes any one of triallyl isocyanurate, triallyl polyisocyanurate, triallyl cyanurate, trimethacrylic acid, diallyl phthalate, divinylbenzene, and multifunctional (meth)acrylate, or a combination of at least two thereof.
[0055] Preferably, the mass percentage of the crosslinking agent in the boron nitride-containing resin composition is ≤20%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16% or 18%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Preferably, the filler includes any one of silicon dioxide, titanium dioxide, barium titanate, strontium titanate, magnesium titanate, calcium titanate, barium strontium titanate, calcium barium titanate, lead titanate, lead zirconate titanate, lead lanthanum zirconate titanate, barium lanthanum titanate, barium zirconate titanate, hafnium dioxide, lead magnesium niobate, barium magnesium niobate, lithium niobate, potassium niobate, strontium aluminum tantalate, potassium tantalum niobate, barium strontium niobate, lead barium niobate, barium titanium niobate, strontium bismuth tantalate, bismuth titanate, barium rubidium titanate, copper titanate, and lead titanate-lead magnesium niobate, or a combination of at least two of them.
[0057] Preferably, the average particle size (D 50 The particle size) is 0.01-50 μm, for example, it can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, and specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively enumerates the specific point values included in the range. It is further preferred to be 0.01-30 μm, and even more preferred to be 0.01-10 μm.
[0058] Preferably, the mass percentage of filler in the boron nitride-containing resin composition is ≤20%, for example, it can be 0, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16% or 18%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] A solvent may also be added to the above-mentioned boron nitride-containing resin composition, and the amount of solvent added is selected by a person skilled in the art based on experience and process requirements, so that the boron nitride-containing resin composition reaches a viscosity suitable for use, so as to facilitate the impregnation and coating of the boron nitride-containing resin composition. In the subsequent drying, semi-curing or complete curing stage, the solvent in the boron nitride-containing resin composition will partially or completely volatilize.
[0060] In another aspect, the present invention provides a resin adhesive, which comprises the boron nitride-containing resin composition as described in the first aspect and a solvent.
[0061] Illustratively, the solvent includes any one of a ketone solvent, an alcohol solvent, an aromatic hydrocarbon solvent, an ester solvent, and a nitrogen-containing solvent, or a combination of at least two thereof.
[0062] The solvent of the present invention is not particularly limited, and generally, ketones such as acetone, butanone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone, aromatic hydrocarbons such as toluene, xylene, and mesitylene, esters such as ethyl acetate, butyl acetate, and ethoxyethyl acetate, alcohols such as methanol, ethanol, and butanol, ethers such as ethyl cellosolve, butyl cellosolve, ethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, carbitol, and butyl carbitol, and nitrogen-containing solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone can be used; the solvent can be used alone or in combination of two or more.
[0063] The boron nitride-containing resin composition provided by the present invention is prepared by the following method, which comprises: mixing and uniformly dispersing the components in the boron nitride-containing resin composition to obtain the boron nitride-containing resin composition.
[0064] In a second aspect, the present invention provides a prepreg, comprising a reinforcing material and the boron nitride-containing resin composition as described in the first aspect attached to the reinforcing material.
[0065] Preferably, the boron nitride-containing resin composition is attached to the reinforcing material by impregnation and drying.
[0066] Preferably, the raw material of the reinforcing material includes any one of natural fibers, organic synthetic fibers, organic fabrics, and inorganic fibers, or a combination of at least two thereof; for example, glass fiber cloth, quartz glass fiber blended cloth, non-woven fabric, quartz cloth, fiber paper, and the like.
[0067] Illustratively, the method for preparing the prepreg is: using the resin glue containing the boron nitride resin composition to impregnate a reinforcing material, and then drying to obtain the prepreg.
[0068] Preferably, the drying temperature is 100-180°C, for example, it can be 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C or 175°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 115-175°C is further preferred.
[0069] Preferably, the drying time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 15 min, 20 min or 25 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 2-15 min is further preferred.
[0070] In a third aspect, the present invention provides a thermally conductive film, wherein the material of the thermally conductive film includes the boron nitride-containing resin composition as described in the first aspect.
[0071] Preferably, the thermally conductive film is prepared by coating the boron nitride-containing resin composition on a release material and then drying and / or semi-curing the composition.
[0072] In a fourth aspect, the present invention provides a metal foil-clad laminate, comprising a metal foil and at least one of the prepreg described in the second aspect and the thermally conductive film described in the third aspect.
[0073] Preferably, the metal foil in the metal foil-clad laminate includes any one of copper foil, aluminum foil, nickel foil, alloy foil, or a combination of at least two of them.
[0074] Preferably, the metal foil is copper foil, and the metal foil-clad laminate is a copper-clad laminate.
[0075] Preferably, the number of prepregs in the metal foil-clad laminate is 1-20, for example, 2, 3, 5, 7, 9, 10, 11, 13, 15, 17 or 19, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0076] Exemplarily, the method for preparing the metal foil-clad laminate comprises: laminating metal foil on one side or both sides of a prepreg and curing to obtain the metal foil-clad laminate; or, stacking at least two prepregs into a laminate, and then laminating metal foil on one side or both sides of the laminate and curing to obtain the metal foil-clad laminate.
[0077] Preferably, the curing is carried out in a press.
[0078] Preferably, the curing temperature is 170-280°C, for example 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0079] Preferably, the curing pressure is 1-10 MPa, for example 1.5 MPa, 2 MPa, 3 MPa, 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa or 9 MPa, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0080] Preferably, the curing time is 30-300 min, for example 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, 150 min, 180 min, 200 min, 220 min, 240 min, 260 min or 280 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0081] In a fifth aspect, the present invention provides a printed circuit board, comprising at least one of the prepreg described in the second aspect, the thermally conductive film described in the third aspect, and the metal foil-clad laminate described in the third aspect.
[0082] Compared with the prior art, the present invention has the following beneficial effects:
[0083] (1) In the boron nitride-containing resin composition provided by the present invention, boron nitride is sintered with a specific type and amount of sintering aid and then crushed. By designing a modification method, the modified boron nitride has a high filling rate in the resin material. The boron nitride-containing resin composition containing the modified boron nitride has not only high thermal conductivity, but also high peel strength and excellent bonding performance, so that the metal foil-clad laminate achieves excellent comprehensive effects in terms of high thermal conductivity and high reliability.
[0084] (2) The present invention designs and optimizes the components and ratios of the boron nitride resin composition so that the thermal conductivity of the copper-clad laminate containing the boron nitride resin composition is ≥5.0 W / m·k and the peel strength is ≥0.75 N / mm, and the copper-clad laminate having the boron nitride resin composition has excellent heat dissipation performance, interlayer bonding strength and reliability. DETAILED DESCRIPTION
[0085] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0086] The preparation method of the modified boron nitride is described below in conjunction with specific preparation examples, but the preparation method of the modified boron nitride is not limited to these preparation examples.
[0087] In the following preparation examples, boron nitride, sintering aids, and other metal oxides are all commercially available chemicals; among them, boron nitride has a lamellar structure and is purchased from 3M, CFP003.
[0088] Preparation Example 1-6
[0089] Modified boron nitride AF, the preparation method is as follows:
[0090] Boron nitride, a sintering aid and optionally other metal oxides are weighed in parts by mass according to the ratio shown in Table 1, and physically dry mixed for 1 hour to obtain a mixture; the mixture is added to a grinding tool, and sintered in a nitrogen atmosphere according to the temperature, pressure and time shown in Table 1 to obtain a sintered product; the sintered product is a block sample, which is placed in a ball mill for wet ball milling at a speed of 3000 rpm for 1-5 hours, and the particle size of the zirconium beads is 1-10 mm; after ball milling, it is dried to obtain modified boron nitride particles; the preparation of modified boron nitride particles with different particle sizes is achieved by controlling the ball milling time.
[0091] Table 1
[0092]
[0093]
[0094] In Table 1, the dosage units of boron nitride (BN), sintering aids, and other metal oxides are "parts" (parts by mass), and "--" means that the component is not added. The average particle size of the modified boron nitride is tested by laser diffraction method, and the testing instrument is Malvern laser particle size analyzer, model MS3000.
[0095] The boron nitride-containing resin composition and the application thereof of the present invention will be described in detail below by taking a number of embodiments as examples, but the boron nitride-containing resin composition and the application thereof are not limited to these embodiments.
[0096] In the following examples, the materials for which the preparation methods are not provided are all commercially available chemicals, and the specific information is shown in the following table:
[0097]
[0098]
[0099] Examples 1-6, Comparative Examples 1-3
[0100] A boron nitride-containing resin composition, the types and amounts of each component are shown in Table 2, and the units of the amount of each component are "parts" (parts by mass).
[0101] A prepreg and a copper-clad laminate comprising the boron nitride-containing resin composition, the preparation method of which is as follows:
[0102] (1) mixing and evenly dispersing the components of the boron nitride-containing resin composition with a solvent (ethylene glycol methyl ether) according to the formula amount to prepare a glue solution with a solid content of 80%; impregnating the glue solution with a glass fiber cloth, placing the glass fiber cloth in an oven at 155° C. and baking it for 5 minutes to obtain a prepreg with a thickness of 5 mil;
[0103] (2) 6 prepregs are stacked, copper foils are stacked on both sides thereof, and the prepregs are laminated and cured in a hot press at 210° C. and 5 MPa pressure for 2 h to obtain the copper clad laminate.
[0104] The copper clad laminate is subjected to a performance test, and the specific method is as follows:
[0105] (1) Thermal conductivity: The thermal conductivity of the plate is tested according to the test method in standard ASTM-D5470;
[0106] (2) Peel strength: Refer to the test conditions in IPC-TM-650 2.4.8 method to test the peel strength of the sheet;
[0107] The performance test data is shown in Table 2.
[0108] Table 2
[0109]
[0110]
[0111] According to the performance test data in Table 2, the modified boron nitride prepared by a specific method in the present invention is compounded with a resin material, so that the boron nitride-containing resin composition and the copper clad laminate prepared therefrom have high thermal conductivity and high peel strength, wherein the thermal conductivity of Examples 1-4 is 5.0-15.0 W / m·k, and the peel strength is 0.75-1.43 N / mm, having excellent comprehensive performance.
[0112] In Example 5, the amount of modified boron nitride used is relatively small, resulting in a decrease in the thermal conductivity of the copper clad laminate; in Example 6, the amount of modified boron nitride used is too large, resulting in poor processability of the composition and failure to prepare a qualified product.
[0113] According to the comparison between Example 2 and Comparative Examples 1-3, the modified boron nitride E in Comparative Example 1 uses too little sintering aid, and its modification effect is not obvious, resulting in the inability of the modified boron nitride E to achieve a high filling ratio, poor processability, and inability to prepare qualified products. Unmodified boron nitride filler is used in Comparative Example 3, and high filling is also impossible, and qualified products cannot be prepared. The modified boron nitride F in Comparative Example 2 uses too much sintering aid, which affects the thermal conductivity of the material, resulting in a significant decrease in the thermal conductivity of the plate.
[0114] The applicant declares that the present invention illustrates the boron nitride-containing resin composition and its application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A boron nitride-containing resin composition, characterized in that: The boron nitride-containing resin composition comprises a combination of a resin material and modified boron nitride; The modified boron nitride is prepared by the following method, which comprises: mixing boron nitride and a sintering aid, sintering and crushing to obtain the modified boron nitride; The sintering aid includes any one of calcium oxide, magnesium oxide, silicon oxide, yttrium oxide, niobium oxide, and potassium feldspar, or a combination of at least two thereof; Based on the total mass of the boron nitride and the sintering aid being 100%, the mass of the sintering aid is 1-10%.
2. The boron nitride-containing resin composition according to claim 1, characterized in that The mixed raw materials also include other metal oxides; Preferably, the other metal oxides include aluminum oxide and / or beryllium oxide; Preferably, based on the total mass of the boron nitride, the sintering aid and the other metal oxides being 100%, the mass of the other metal oxides is 1-10%.
3. The boron nitride-containing resin composition according to claim 1 or 2, characterized in that: The sintering is carried out in an inert atmosphere; Preferably, the inert atmosphere comprises a nitrogen atmosphere and / or an argon atmosphere; Preferably, the sintering temperature is 700-2000°C; Preferably, the sintering pressure is 1-10 GPa; Preferably, the sintering time is 2-8 hours.
4. The boron nitride-containing resin composition according to any one of claims 1 to 3, characterized in that The average particle size of the modified boron nitride is 0.1-30 μm; Preferably, the mass percentage of modified boron nitride in the boron nitride-containing resin composition is 30-92%, and more preferably 50-90%.
5. The boron nitride-containing resin composition according to any one of claims 1 to 4, characterized in that: The resin material includes any one of epoxy resin, cyanate resin, polyphenylene ether resin, polybutadiene resin, butadiene-styrene resin, bismaleimide-triazine resin, bismaleimide resin, polytetrafluoroethylene resin, polyimide resin, phenolic resin, phenoxy resin, acrylic resin, liquid crystal resin, benzoxazine resin, and nitrile rubber, or a combination of at least two thereof; Preferably, the mass percentage of the resin material in the boron nitride-containing resin composition is 8-80%, more preferably 9-50%.
6. The boron nitride-containing resin composition according to any one of claims 1 to 5, characterized in that: The boron nitride-containing resin composition further comprises any one or a combination of at least two of an accelerator, an initiator, a crosslinking agent, a filler, a flame retardant, and a curing agent; Preferably, the accelerator comprises any one or a combination of at least two of imidazole compounds, organic complexes, tertiary amines, tertiary phosphines, and quaternary ammonium salts, and imidazole compounds are further preferred; Preferably, the imidazole compound includes any one of 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 2-heptadecylimidazole, 2-isopropylimidazole, 2-phenyl-4-methylimidazole, 2-dodecylimidazole, and 1-cyanoethyl-2-methylimidazole, or a combination of at least two thereof; Preferably, the mass percentage of the accelerator in the boron nitride-containing resin composition is ≤8%; Preferably, the initiator includes any one of an organic peroxide, an azo initiator, and a carbon-based initiator, or a combination of at least two thereof; Preferably, the organic peroxide includes any one of α,α'-di(tert-butylperoxy-m-isopropylbenzene)benzene, diisopropylbenzene peroxide, tert-butylperoxy-isopropylbenzene, bis(tert-butylperoxy-isopropyl)benzene, 1,1-bis(tert-hexylperoxide)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hex-3-yne, tert-butyl peroxyoctanoate, and tert-butyl peroxybenzoate, or a combination of at least two thereof; Preferably, the mass percentage of the initiator in the boron nitride-containing resin composition is ≤8%; Preferably, the crosslinking agent includes any one or a combination of at least two of triallyl isocyanurate, triallyl polyisocyanurate, triallyl cyanurate, trimethacrylic acid, diallyl phthalate, divinylbenzene, and multifunctional (meth)acrylate; Preferably, the mass percentage of the crosslinking agent in the boron nitride-containing resin composition is ≤20%; Preferably, the filler comprises any one of silicon dioxide, titanium dioxide, barium titanate, strontium titanate, magnesium titanate, calcium titanate, barium strontium titanate, calcium barium titanate, lead titanate, lead zirconate titanate, lead lanthanum zirconate titanate, barium lanthanum titanate, barium zirconate titanate, hafnium dioxide, lead magnesium niobate, barium magnesium niobate, lithium niobate, potassium niobate, strontium aluminum tantalate, potassium tantalum niobate, barium strontium niobate, lead barium niobate, barium titanium niobate, strontium bismuth tantalate, bismuth titanate, barium rubidium titanate, copper titanate, and lead titanate-lead magnesium niobate, or a combination of at least two thereof; Preferably, the mass percentage of filler in the boron nitride-containing resin composition is ≤20%.
7. A prepreg, characterized in that: The prepreg comprises a reinforcing material and a boron nitride-containing resin composition according to any one of claims 1 to 6 attached to the reinforcing material; Preferably, the boron nitride-containing resin composition is attached to the reinforcing material by impregnation and drying.
8. A thermally conductive film, characterized in that: The material of the thermally conductive film comprises the boron nitride-containing resin composition according to any one of claims 1 to 6; Preferably, the thermally conductive film is prepared by coating the boron nitride-containing resin composition on a release material and then drying and / or semi-curing the composition.
9. A metal foil-clad laminate, characterized in that: The metal foil clad laminate comprises a metal foil and at least one of the prepreg according to claim 7 and the thermally conductive film according to claim 8 .
10. A printed circuit board, characterized in that: The printed circuit board comprises at least one of the prepreg according to claim 7, the thermally conductive film according to claim 8, and the metal foil-clad laminate according to claim 9.
Citation Information
Patent Citations
Method for preparing highly heat-conductive copper-clad plate
CN101767481A
High thermal conductivity copper clad plate and preparation method thereof
CN110370750A
Low-dielectric high-thermal-conductivity polytetrafluoroethylene high-frequency copper-clad plate and preparation method thereof
CN115556439A
Boron nitride aggregate, thermosetting resin composition containing boron nitride aggregate, and applications thereof
CN109988409A
Resin composition and resin glue solution containing resin composition, prepreg, laminated board, copper-clad plate and printed circuit board
CN112552630A
Cited By
Full-bio-based epoxy resin composite material based on cardanol modified boron nitride and preparation method of full-bio-based epoxy resin composite material
CN120682445A
A full-bio-based epoxy resin composite material based on cashew phenol modified boron nitride and a preparation method thereof
CN120682445B